2010
DOI: 10.1159/000322590
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Increases Plasma Levels of Corticotropin-Releasing Hormone in Rats

Abstract: Background: Corticotropin-releasing hormone (CRH) is expressed in the brain, immune cells and the gut, where gene expression is upregulated by lipopolysaccharide (LPS) 6 h after injection. Whether these changes are reflected by increased circulating levels of CRH and adrenocorticotropic hormone (ACTH) is unknown. Methods: LPS (100 µg/kg) was injected intraperitoneally in conscious rats, and blood processed for CRH using the new RAPID (reduced temperatures, acidification, protease inhibition, isotopic exogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 109 publications
2
17
0
Order By: Relevance
“…These data are consistent with previous reports showing a long-lasting reduction of gastric transit of liquid or solid induced by peripheral injection of LPS at similar or lower doses in rats (6,19,64). Under these conditions, peripheral injection of the long-lasting CRF 2 receptor antagonist astressin 2 -B (52) further enhanced the inhibitory effect of LPS by 31%.…”
Section: Functional Role Of Ucn/crf 2 Activation In the Gastric-emptysupporting
confidence: 92%
See 1 more Smart Citation
“…These data are consistent with previous reports showing a long-lasting reduction of gastric transit of liquid or solid induced by peripheral injection of LPS at similar or lower doses in rats (6,19,64). Under these conditions, peripheral injection of the long-lasting CRF 2 receptor antagonist astressin 2 -B (52) further enhanced the inhibitory effect of LPS by 31%.…”
Section: Functional Role Of Ucn/crf 2 Activation In the Gastric-emptysupporting
confidence: 92%
“…Next, we delineated the expression of Ucns and CRF 2b in multiple defined layers of the GC, including myenteric neurons, using the laser capture microdissection (LCM) system combined with reverse transcription polymerase chain reaction (RT-PCR). The regulation of Ucns/CRF 2b gene expression in the gastric mucosa and SϩM over a 24-h period was assessed following LPS injected intraperitoneally at a single dose of 100 g/kg previously established to reduce gastric emptying (4,19,64), mimicking some of the clinical features of acute Gramnegative bacterial infection without apparent signs of severe sickness found in endotoxin shock induced by milligram doses of LPS (38). Previously, we identified in the rat esophagus and lower esophagus sphincter (LES) the novel CRF 2 splice variant CRF 2a and the other related isoform CRF 2a-3 , which contains the entire intron 3 (67).…”
mentioning
confidence: 99%
“…2A). Accordingly to previous data in the bibliography by using the same antibody, NUCB2 detection in gastric mucosa by western blot image showed a double band at 50 kDa (Goebel et al, 2011;Li et al, 2012;Riva et al, 2011;Stengel et al, 2009). Measurements of the gastric NUCB2/nesfatin-1 expression showed that the mRNA levels of NUCB2 were significantly higher just after the weaning, i.e., at 4 weeks of age (1.00 ± 0.05 at 2 weeks, 1.41 ± 0.10 at 4 weeks vs 1.29 ± 0.13 at 6 weeks and 1.14 ± 0.09 at 8 weeks arbitrary units; *p ≤ 0.05 vs 2-weeks-old) (Fig.…”
Section: Age-associated Variations In Nucb2/nesfatin-1 Levelssupporting
confidence: 78%
“…The underlying mechanisms of acute stress-related reduction of food intake are largely linked to the activation of corticotropin releasing factor (CRF) signaling pathways. It is well documented that various stressors including wrap restraint stress, low dose of lipopolysaccharide, or abdominal surgery activate the hypothalamic/CRF-pituitary-adrenal axis as shown by Fos or Fos/CRF colabeling in stress-responsive hypothalamic regions and the related elevation of circulating adrenocorticotropic hormone (ACTH) and corticosterone (8,19). Moreover, CRF and the related peptides urocortin 1 or urocortin 2 injected centrally or peripherally reduce feeding via activation of brain CRF receptor subtypes 1 (CRF 1 ) and 2 (CRF 2 ) and peripheral CRF 2 receptor in rats (48,67,71).…”
mentioning
confidence: 99%